Advertisements

Question 1. Factorize -3 x 2 y − 3 x + 9 x y 2

Question 1. Factorize  -3x ^{2}y-3x+9xy ^{2}

— algebra

Solution:

-3x ^{2}y-3x+9xy ^{2}

To factorize this expression we can see that 3x is common term among all three terms of the expression – which we take out and put brackets around the remaining factor.

-3x ^{2}y-3x+9xy ^{2}

=3x(-xy-1+3y ^{2})

 

Check:

so, 3x and (-xy-1+3y ^{2}) are two factors of the given expression. If both multiplied like below;

3x (-xy-1+3y ^{2})= 3x.(-xy)-3x.1+3x.3y ^{2} =-3x2y-3x+9xy ^{2}

i-e same original expression we get.

 

 

 


  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  

You may submit a MCQ or maths problem with solution tips here in the comment box below! If you could not solve anyone, you may submit a MCQ or maths problem without solution as well. We will try our level best to solve it for you!

Your email address will not be published.

You may use these <abbr title="HyperText Markup Language">HTML</abbr> tags and attributes: <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>

All original content on these pages is fingerprinted and certified by Digiprove
Insert math as
Block
Inline
Additional settings
Formula color
Text color
#333333
Type math using LaTeX
Preview
\({}\)
Nothing to preview
Insert